Hannah Cribben - Thesis submitted in partial fulfilment of the degree of doctor of clinical psychology (DClinPsych) - Cribben, H (2023)
ABSTRACTS SYSTEMATIC REVIEW OF THE LITERATURE TITLE: THE EFFECTIVENESS AND ACCEPABILITY OF PARENTING INTERVENTIONS TO REDUCE THE RISK OF CHILD MALTREATMENT IN THE UK: A SYSTEMATIC REVIEW Objectives: Evidence regarding the effectiveness and acceptability of parenting programs to reduce maltreatment in the UK is limited; there are no NICE guidelines for these interventions, and it is an area consistently highlighted as needing further research. This systematic review aimed to evaluate the effectiveness and acceptability of parenting interventions in the UK based on reported outcome measures and uptake/drop-out data. Method: Five databases were searched and PRISMA guidelines were followed throughout. Studies were included if they were published in a scientific journal or official report, were based in the UK, evaluated an intervention for reducing the risk of child maltreatment with parents/caregivers of a child aged 0-17, and reported quantitative outcomes relating to the impact of the intervention. Results: 19 studies were identified for inclusion in this review. The interventions were based on a range of theoretical underpinnings and evaluated for use with heterogeneous populations including specific at-risk samples, maltreating parents, and the general population. Conclusion: The existing evidence is not robust enough to draw firm conclusions regarding the effectiveness and acceptability of parenting interventions to reduce child maltreatment in the UK. Further gold-standard research is needed to inform evidence-based guidelines.